PERILAKU NUTRISI IBU HAMIL DENGAN HIPERTENSI DI RSUD BANGIL KABUPATEN PASURUAN - Tri Nataliswati; Langen Basuki Abrianto (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2022)
Hypertension in pregnancy is a disorder of unknown etiology, formerly called ’toxemia of pregnancy’ or pre-eclampsia. One of the causes of hypertension in pregnant women is the wrong diet. The nutritional behavior of pregnant women during pregnancy is very important because the lack of knowledge, attitudes and actions of mothers in meeting their nutritional needs during pregnancy results in disturbances in pregnancy or the fetus. This study uses a descriptive method that aims to determine the nutritional behavior of pregnant women with hypertension in Bangil Hospital, Pasuruan Regency. Sampling using accidental sampling technique with a sample of 30 respondents. The instrument used is a closed questionnaire. The results of the study were the nutritional behavior of pregnant women with hypertension as many as 18 respondents (60%) well behaved. It is expected that pregnant women will be more active in improving their behavior the better by seeking information about healthy nutritional needs for pregnant women with hypertension, for example actively participating in counseling activities and through information media such as books or magazines about nutrition for pregnant women. Keywords : Behavior, Nutritional, Pregnancy Women, Hypertension